Serum levels of folate, 25‐hydroxyvitamin D3 and cobalamin during UVB phototherapy: findings in a large prospective trial. (8th October 2019) - Weber, B.; Marculescu, R.; Radakovic, S.; Tanew, A.
Abstract: Background: Narrowband UVB phototherapy (NB‐UVB) is a mainstay in the treatment of numerous inflammatory dermatoses. Whereas, a wealth of studies has shown that NB‐UVB treatment increases 25‐hydroxyvitamin D3 (25(OH)D) levels, only sparse and controversial data exist on its effect on serum folate and cobalamin. Objectives: To determine whether exposure to NB‐UVB alters serum folate or cobalamin levels. Methods: A single‐centre, prospective, open observational study on 101 patients subjected to NB‐UVB phototherapy between late fall and early spring. Serum folate, 25(OH)D and cobalamin levels were measured after 0, 12, 24 and 36 NB‐UVB exposures. Results: After 12 NB‐UVB exposures a significant decrease of mean serum folate (−1.0 nmol/L; P = 0.03) and cobalamin (−14.5 pmol/L, P = 0.03) levels was observed whereas serum levels of 25(OH)D showed a significant increase (35.4 nmol/L, P < 0.0001). Conclusions: A standard course of NB‐UVB induces a small but significant decrease of serum folate and cobalamin levels.